2021
DOI: 10.1038/s41598-021-95413-9
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle is associated with exercise tolerance evaluated by cardiopulmonary exercise testing in Japanese patients with chronic obstructive pulmonary disease

Abstract: Decreasing exercise tolerance is one of the key features related to a poor prognosis in patients with chronic obstructive pulmonary disease (COPD). Cardiopulmonary exercise testing (CPET) is useful for evaluating exercise tolerance. The present study was performed to clarify the correlation between exercise tolerance and clinical parameters, focusing especially on the cross-sectional area (CSA) of skeletal muscle. The present study investigated 69 patients with COPD who underwent CPET. The correlations between… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Thus, sarcopenia was found in 20 % of COPD patients with GOLD 1-2 severity, and in 40 % of the patients with . This fact is confirmed by the established direct correlation between exercise tolerance and skeletal muscle function in patients with COPD depending on the GOLD stage [22]. This dependence is also observed in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, sarcopenia was found in 20 % of COPD patients with GOLD 1-2 severity, and in 40 % of the patients with . This fact is confirmed by the established direct correlation between exercise tolerance and skeletal muscle function in patients with COPD depending on the GOLD stage [22]. This dependence is also observed in our study.…”
Section: Discussionsupporting
confidence: 92%
“…First, this was a single-center study with a small number of patients, and the number of female patients was disproportionately low. Second, detailed evaluation of O 2 delivery-utilization in skeletal muscles was not performed in the present study, although it has been reported that the skeletal muscle area measured by computed tomography correlates with ventilatory efficiency during CPET [31], and hence, would have correlated with O 2 extraction during exercise in the present study and our previous study [19]. Third, the study included some COPD patients who regularly took short-acting muscarinic antagonists rather than long-acting muscarinic antagonists, and the number of patients receiving dual or triple therapy including inhalation therapy was low, which might have affected the results.…”
Section: Discussionmentioning
confidence: 93%
“…Results on the incremental shuttle walk test and 6 min walking distance, muscle function measured by handgrip force and quadriceps force, and symptoms such as dyspnea are also associated with physical activity in patients with COPD [ 57 , 65 ]. Briefly, skeletal muscle is positively associated with exercise capacity as assessed by 6 min walking distance and oxygen uptake at peak exercise measured by cardiopulmonary exercise testing in patients with COPD [ 66 , 67 ]. Interestingly, the cross-sectional area of skeletal muscle measured by computed tomography is positively associated with physical activity [ 67 ], showing that exercise capacity involves physical activities via skeletal muscle mass.…”
Section: Physical Activity and Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%
“…Importantly, exercise can exacerbate the phenomena [ 113 ] that might contribute to avoidance of moderate or vigorous physical activity and increase sedentary behavior. Even worse, the sequence of behavior induces a negative feedback cycle leading to poor outcomes for COPD patients, because increasing sedentary time with a reduction in physical activity contributes to skeletal muscle atrophy, especially in antigravity muscles such as the erector spinae muscles and thigh muscles, causing weight loss and decreased exercise capacity [ 59 , 66 , 67 , 114 ]. Consequently, the symptoms of dyspnea and shortness of breath are induced at a low intensity of physical activity, and patients try to avoid movement along with progression of muscle atrophy.…”
Section: Clinical Impact Of Sedentary Behavior In Patients With Chron...mentioning
confidence: 99%